2013
DOI: 10.2174/1874226201306010001
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles and their Roles in Inflammation: A Review§

Abstract: Microparticles (MPs) were long dismissed as "platelet-dust", cell debris, with no functional significance. Theyare anucleated vesicles (0.1μm to 1μm), enclosed in a membrane, secretedinto the circulation by cells during cell activation or apoptosis. They have now emerged as mediators and markers of inflammatory diseases and autoimmune disorders. They are distinctly different from exosomes and apoptotic bodiesand are released from nearly every cell type, the most abundant being platelets, leukocytes and endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 78 publications
(137 reference statements)
0
12
0
1
Order By: Relevance
“…Interestingly, leukocyte-derived microparticles (CD66b +) appears to carry an endogenous anti-inflammatory effect ( Batool et al, 2013 ). We observed a significant increase in their levels in the post decompression dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, leukocyte-derived microparticles (CD66b +) appears to carry an endogenous anti-inflammatory effect ( Batool et al, 2013 ). We observed a significant increase in their levels in the post decompression dataset.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is based on the recently accumulated knowledge about small particles (microparticles or microvesicles) shed by different cells in an organized and regulated manner. Such microparticles (MPs), which carry various nuclear components of their originating cells, like RNA and DNA, are involved in cell signaling and communication, and have recently emerged as relevant markers of inflammatory diseases (Batool et al, 2013). Variations in their levels and the cells from where they originated have been linked to an increasing range of diseases and inflammatory processes (Cognasse et al, 2015) (Puddu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some important antigenic markers on MPs are summarized in Table 1, and techniques for analyzing them are summarized in Table 2 and are reviewed in Ref. 15.…”
Section: Mechanisms Of Ev Formationmentioning
confidence: 99%
“…Well-documented contributors to the increased cardiovascular risk in patients with ESRD and CKD are endothelial dysfunction, arterial stiffness, and accelerated atherosclerosis (5,6,55). The endothelial dysfunction in ESRD may partly arise (5) as a result of the damaging effect of endotheliumderived EVs on the endothelial cells themselves, and the involvement of EVs in cardiovascular disease has been comprehensively reviewed elsewhere (15,125,126,137,144). Both in patients with preexisting coronary artery disease (152) and in hypertensive patients with impaired renal function, it has been shown that there is an increase in circulating apoptotic EMPs (defined as CD31ϩ/annexin Vϩ EMP) (71,73).…”
Section: Effect Of Mirs Within Evs On Apoptosismentioning
confidence: 99%
“…Microparticles are inflammatory buddings from cells (between 0.1 and 1 μm) [ 2 ], which themselves sustain the inflammatory reaction in autoimmune disease [ 3 ]. Microparticles are released from activated, apoptotic or dying cells by a process called blebbing whereby membrane remodelling modification and phosphatidylserine exposure result in an extrusion incorporating parental surface proteins and contents [ 4 ].…”
Section: Introductionmentioning
confidence: 99%